Mathematical Modeling of Plastic Deformation of a Tube from Dispersion-Hardened Aluminum Alloy in an Inhomogeneous Temperature Field - Oleg Matvienko; Olga Daneyko; Tatiana Kovalevskaya (Crystals, 2020)
The effect of temperature distribution on a stress–strain state tube made of disperse-hardened aluminum alloy subjected to internal pressure was investigated. The mathematical model is based on equations of physical plasticity theory and principles of mechanics of deformable solids. The results of this investigation demonstrate that varying the outer wall temperature in the range of 200 K at a fixed temperature of the inner wall leads to a significant change in the plastic resistance limit (for the considered tube sizes, this change is approximately 15%). An increase of the tube wall temperature reduces the resistance to plastic deformation. For the same absolute temperature difference between the outer and inner walls, the plastic resistance limit is less for the higher temperature of the inner wall of the tube. A decrease of the distances between the hardening particles at the same volume fraction of second phase leads to a significant increase in the pressure required to achieve plastic deformation of the tube walls. An increase in tube wall temperature reduces the resistance to plastic deformation. For the same absolute temperature difference between the outer and inner walls, the plastic resistance limit is lower for the higher temperature of the inner tube wall. The decrease of the distance between the hardening particles at the same volume fraction of the second phase leads to a significant increase in the pressure required to achieve plastic deformation of the tube walls.